Incremental Benefit of Achieving Endoscopic and Histologic Remission in Patients with Ulcerative Colitis: A Systematic Review and Meta-Analysis - Yoon, Hyuk (Gastroenterology, 2020)
BACKGROUND & AIMS: Clinical remission, defined by a composite of patient reported outcomes and Mayo endoscopy subscore (MES) 0 or 1 is a recommended treatment target in patients with ulcerative colitis (UC). We estimated whether incorporating more rigorous remission definitions, of endoscopic remission (MES 0) and histologic remission, affects risk of relapse. METHODS: Through a systematic review, we identified cohort studies in adults with UC in clinical remission that reported a minimum 12-month risk of clinical relapse, based on MES (0 vs 1) and/or histologic disease activity, in patients with endoscopic remission. Using random effects meta-analysis, we calculated relative and absolute risk of clinical relapse in patients with UC achieving different treatment targets. RESULTS: In a meta-analysis of 17 studies that included 2608 patients with UC in clinical remission, compared to patients achieving MES 1, patients achieving MES 0 had a 52% lower risk of clinical relapse (relative risk, 0.48; 95% CI, 0.37–0.62). The median 12-month risk of clinical relapse in patients with MES 1 was 28.7%; the estimated annual risk of clinical relapse in patients with MES 0 was 13.7% (95% CI, 10.6–17.9). In a meta-analysis of 10 studies in patients in endoscopic remission (MES 0), patients who achieved histologic remission had a 63% lower risk of clinical relapse vs patients with persistent histologic activity (relative risk, 0.37; 95% CI, 0.24–0.56). Estimated annual risk of clinical relapse in who achieved achieving histologic remission was 5.0% (95% CI, 3.3–7.7). CONCLUSIONS: In a systematic review and meta-analysis of patients with UC in clinical remission, we observed that patients achieving more rigorous treatment endpoints (endoscopic and histologic remission) have a substantially lower risk of clinical relapse compared with patients achieving clinical remission.